From environmental ethics to human ecology. A necessary change - Marcos, Alfredo; Valera, Luca (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
Environmental ethics was born as a fair response to the excesses of anthropocentrism. However, an obsessive emphasis on ethics and the environment, with the consequent neglect of the anthropological, may be damaging human life, the freedom of people and life in general. We advocate here for the construction of a human ecology that goes beyond and deeper than the environmental ethics to use. We defend that humanism is perfectly compatible with the recognition of the inherent value of all natural beings. We do this based mainly on some ideas of Hans Jonas, although we reject his catastrophic heuristics. From him we return to the idea that there is a moral responsibility towards other living beings, starting with those closest in time and space, and towards the free flourishing of today’s people. With this, too, the weight of ethics on our ecological action is lowered. This has to attend mainly to experiential, anthropological, scientific and common sense criteria. Finally, we defend that politics, education and environmental communication should be directed directly towards the freedom and virtuous development of today’s people, and not towards controlling them through blame. The transition from environmental ethics to human ecology —we conclude— can be beneficial for both people and nature.